STUDENTS’ PERCEPTION OF “ENGLISH FOR NURSING” USED AT KOLAKA NURSING ACADEMY - Nasmah Riyani (Universitas Sembilanbelas November Kolaka, 2016)
The objectives of this study were: to identify the students’ perception of “English for Nursing” module, to investigate to the extent to which existing syllabus and module have covered those needs, and to select materials that are relevant to students’ needs of English at the same institution. The study adopted a qualitative method and was designed as a survey study. Conducted at the Nursing Academy in Kolaka, the study involved 30 subjects, which were selected through a simple random sampling method. The instruments of the study were questionnaires, interview guidelines, documents, audio-visual materials, and field notes. The result of the study indicate that: the students tended to find the module used by the teacher difficult. Meanwhile, in target situations students are demanded to master certain skills, particularly writing and nursing technical terms, as well as the ability to communicate with others in order to obtain and provide information accurately. In terms of syllabus, the one being used in Nursing Academy does yet not cover an area of nursing itself. It can be concluded that the students’ perception for English in the Nursing Academy include writing and speaking skills needed to support their profession in the future, so, for this reason, it is necessary that the course syllabus and module are made more specific in the nursing area.